AC breakdown performance of organic transformer oil using different nano oxide fillers of ZnO, NiO and α-Fe2O3 - Dzhahirul, Zamri; N. H., Nik Ali; Muhammad, Umair; Ahmad Syakirin, Ismail @ Rosdi; N., Azis; F. N., Alhabill; M. H., Mamat (Penerbit UTHM, 2024)
The AC breakdown performance of traditional insulating oils in transformers is often inadequate, leading to operational inefficiencies and environmental concerns. There is a growing need for alternatives that enhance transformer performance while being environmentally sustainable. This paper investigates the AC breakdown performance of organic transformer oil, specifically using vegetable oil, mixed with Iron Oxide Hematite (α-Fe2O3), Zinc Oxide (ZnO), and Nickel Oxide (NiO) nanoparticles (NPs). These NPs are incorporated into the organic transformer oil to form Nano Fluids (NFs). The study examines the effect of NPs with different concentrations on the AC breakdown voltage (AC-BDV) of organic transformer oil. The One Minute Power Frequency Test is employed to test the AC-BDV, while X-ray diffraction (XRD) characterizes the structural properties of the NPs. The results indicate that NFs containing 6g of (α-Fe2O3) NPs and 6g of (ZnO) NPs exhibit the most significant improvement in AC-BDV, showing enhancements of approximately 49.86% and 40.17%, respectively. Furthermore, NFs based on (α-Fe2O3) with a concentration of 0.01g/ml outperform other NPs, demonstrating an average breakdown voltage of 13.525 kV. Consequently, the experimental analysis concludes that (α-Fe2O3) based NFs offer effective electrical insulation, serving as a potential substitute for mineral oil in transformers. This innovation not only improves transformer performance but also aligns with environmental concerns, particularly the shift from mineral oil to biodegradable options like organic transformer oil. Different types of nanoparticles and their concentrations directly impact the AC breakdown voltage, underscoring the potential of nanoparticle-infused organic transformer oil in transforming traditional insulating systems.